RELATIONSHIP BETWEEN OHS COMPLIANCE AND HOUSEKEEPING IMPLEMENTATION WITH OCCUPATIONAL INJURY RISK IN A CONSTRUCTION COMPANY - Ardhani, Adinda Novia; Widajati, Noeroel; Ameiliawati, Rika (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Construction companies are one of the highest accident-prone fields. One of the efforts to protect the safety and health of construction workers is OHS compliance from the aspect of compliance in using PPE, following work instructions and implementing routine and periodic housekeeping. OHS compliance and housekeeping implementation to prevent the risk of work accidents. However, based on conditions in the field, many workers still do not comply with OHS and have not implemented housekeeping properly. Purpose: To determine the relationship between OHS compliance, housekeeping implementation, and occupational injury risk in a construction company. Method: This study was an observational study type using a cross-sectional approach. A total of 98 people were used in the sample for this study. Data analysis was performed using the phi test and contingency coefficient test. Result: There is a relationship (p=0,000) with a strong relation (phi=0.959) between OHS compliance and occupational injury risk, and there is a relationship (p=0,000) with a moderate level of relationship (r=0.583) between the housekeeping implementation levels and occupational injury risk for the construction company workers. Conclusion: There is a strong relation between OHS compliance and occupational injury risk and a relatively strong relation between housekeeping implementation levels and occupational injury risk in construction company workers.